Pengaruh Promosi, Harga, dan Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Yamaha di DKI Jakarta - Quranis Siva, Dahliana; Abdullah , Zed (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
ABSTRACT This research aims to analyze the influence of promotion, price and brand image on purchasing decisions for Yamaha motorbikes in DKI Jakarta. This research uses a quantitative method with a positivism approach which considers reality as something single and can be measured with valid and reliable instruments. Data was collected through a questionnaire distributed to respondents who were Yamaha motorbike consumers in DKI Jakarta. The research results show that partially, promotions have a significant negative effect on purchasing decisions for Yamaha motorbikes in DKI Jakarta. The t-statistic value for the influence of promotions on purchasing decisions is -2.053 with a p-value of 0.020, which means the hypothesis is accepted. Price also has a significant influence on purchasing decisions. The t-statistical value for the influence of price on purchasing decisions is 2.237 with a p-value of 0.013, so the hypothesis is accepted. Brand image has the strongest influence on purchasing decisions with a t-statistic value of 6.596 and a p-value of 0.000, which shows that this hypothesis is very significant. Keywords : Promotion; Price; Brand Image; Purchase Decision